PENGGUNAAN GEOCELL UNTUK STABILISASI DAN PERLINDUNGAN EROSI PADA LERENG - Wijaya, Hendy; Gregorius Sandjaja Sentosa; Tascia Adde Marcellia; Aniek Prihatiningsih; Ricky Putra (JMTS: Jurnal Mitra Teknik Sipil, 2023)
The world of construction is experiencing continuous development, in its development, there are many methods of carrying out modern construction, one of which is about strengthening slopes to increase the safety factor of slope stability. Slopes are natural or man-made contours or reliefs that can occur because of construction projects. In its development, one method for increasing slope stability for modern construction is using geocells. Geocell is an artificial material that can protect a slope from erosion factors and add a safety factor for slope stabilization. Geocell was developed by the US Army Corps of Engineering (USACE) in 1970, made from high density polyethylene (HPDE), and there are two types of geocell, namely smooth and rough. This research uses a comparison of several studies to show or determine the effectiveness and usefulness of geocells on a slope. It was found that the use of geocells can increase the erosion resistance of a slope to external factors and increase the safety factor of slope stability. However, the increase in slope stability due to the installation of geocells is also influenced by many factors, such as the characteristics or size of the geocells, the depth of the geocell installation, the characteristics of the soil, and the number of geocell installations. Based on research, it was concluded that the installation of geocells, although proven to increase safety factors from 0.789 to 1.7054, also requires consideration of environmental conditions and slope conditions. For this reason, it is necessary to review or re-inspect the field conditions for the geocell installation location. Abstrak Dunia konstruksi mengalami perkembangan terus menerus, dalam perkembangannya, terdapat banyak cara metode pelaksanaan konstruksi modern, salah satu konstruksi adalah mengenai perkuatan lereng untuk meningkatkan faktor keamanan kestabilan suatu lereng. Lereng merupakan kontur atau relief alami maupun buatan manusia yang bisa terjadi akibat adanya proyek konstruksi, dalam perkembangannya, salah satu metode untuk meningkatkan kestabilan lereng untuk konstruksi modern adalah menggunakan geocell. Geocell merupakan material buatan yang dapat melindungi suatu lereng dari faktor erosi serta menambah faktor keamanan untuk stabilisasi lereng. Geocell dikembangkan oleh US Army Corps of Enginnering (USACE) pada tahun 1970, terbuat dari bahan High Density Polyethylene (HPDE). Penelitian ini menggunakan perbandingan beberapa penelitian untuk menunjukkan atau menentukan efektifitas dan kegunaan geocell dalam suatu lereng. Ditemukan bahwa kegunaan geocell dapat meningkatkan ketahanan erosi suatu lereng terhadap faktor eksternal dan meningkatkan faktor keamanan stabilitas lereng. Akan tetapi, peningkatan stabilitas lereng akibat pemasangan geocell juga dipengaruhi oleh banyak faktor, seperti karakteristik atau ukuran geocell, kedalaman pemasangan geocell, karakteristik tanah, dan jumlah pemasangan geocell. Berdasarkan penelitian, ditemukan kesimpulan bahwa pemasangan geocell, walaupun terbukti meningkatkan faktor keamanan, yaitu peningkatan dari nilai 0,789 menjadi 1,7054, akan tetapi juga perlu dipertimbangkan kondisi lingkungannya dan kondisi lereng eksisting. Untuk itu, diperlukan peninjauan atau inspeksi ulang terhadap kondisi lapangan untuk lokasi pemasangan geocell.